Karakteristik Pengguna Mobile Banking di Kota Bengkulu - Septi Handayani; Merri Anitasari (UNIVED Press, 2022)
The aims of this research is to analyze demographic characteristics, social characteristics, economic characteristics, and cultural characteristics mobile banking users at Bengkulu. This study uses a questionnaire as an instrument to take sample of 100 respondents who use mobile banking services at Bengkulu. The sampling method used is accidental sampling. The analytical method used in this study is qualitative descriptive analysis and crosstab analysis. The results of the study indicate that, respondents were dominated by women who worked as civil servants. Using mobile banking services can help simplify their work in banking transaction. They used the mobile banking service for 3 years, meaning that mobile bankig service users in this study have long interacted with mobile banking service.